The preventive effect of ellagic acid on brain damage in rats via regulating of Nrf-2, NF-kB and apoptotic pathway - Aslan, Abdullah; Gok, Ozlem; Beyaz, Seda; Arslan, Emre; Erman, Orhan; Agca, Can Ali (Wiley, 2020)
The aim of this study was to investigate the neuroprotective role of ellagic acid (EA) on CCl4-induced brain injury in rats. In this study, the rats were divided into four groups. Groups: (1) Control group; (2) EA group; (3) CCl4 group; (4) EA + CCl4 group. In brain tissue, tumor necrosis factor-alpha (TNF-alpha), nuclear factor kappa b (NF-kB), cyclooxygenase-2 (COX-2), nuclear erythroid related factor 2 (Nrf-2), cysteine-aspartic acid protease (caspase-3), VEGF (vascular endothelial growth factor) and B-cell lymphoma-2 (bcl-2) protein expression levels were analyzed by western blotting. MDA (malondialdehyde), catalase enzyme activity (CAT) and glutathione (GSH) analysis were determined by spectrophotometer. In our findings, EA ameliorated Nrf-2 and caspase-3 protein expression levels, GSH and catalase activities, NF-kB, TNF-alpha, VEGF, Bcl-2, COX-2 protein expression levels and MDA levels in CCl4 intoxicated rats. These results suggest that EA demonstrated the neuroprotective effect on CCl4-induced brain damage in rats. Practical applications Ellagic acid has different biological activities, these are; antioxidant, anti-inflammatory, antidepressant, antifibrosis, anticancer, neuroprotective and hepatoprotective. For example it was reported that EA protects the cells against DNA injury induced by free radicals and it can prevent the traumatic brain injury. These results obtained from this study reveals that EA has a protective effect against rat brain damage and it may be used as an alternative drugs for the brain injury treatment in future.
Keywords: brain damage; carbon tetrachloride; COX-2; ellagic acid; Nrf-2; VEGF